Potential of Regulation of Slum Area in The Village Meranti Pandak Pekanbaru City - Putri, LD; ., Harsini; Nasution, S R (International Journal of Engineering and Technology, 2018)
The slum area of Meranti Pandak is one of seven slum areas in Pekanbaru City according to Mayor's Decree No. 151/2016, is on the edge of the vulnerable Siak River with overflow due to ups and downs . This study aims to produce a draft slum area design direction as one of the references for related parties to create Pekanbaru free from slum. The research method used is quantitative research method using secondary data as well as primary data with data collection techniques through observation and filling questionnaire . Result of requirement analysis of structuring slums are the three aspects structuring approach settlement infrastructure; improvements to environmental road accessibility, drinking water services , sanitation access fulfillment,wastewater management and waste management and fire hazard security, enhanced oversight of the development of settlement development from internal parties; LKM, TIPP, POKJA and internal resource team as well as from external parties; college, consult's, government and private sectors as well as community empowerment methods; counseling, mentoring and technical assistance.